Direct and deferred sediment-transport events and seafloor disturbance induced by trawling in submarine canyons - Palanques, Albert (2024)
Bottom trawling on marine environments can drastically modify seafloor geomorphology and sedimentary dynamics not only on the fishing grounds but also in adjacent downslope regions, particularly in submarine canyons environments, which are hotspots of benthic biomass and productivity in the deep sea. When this type of fishery occurs along submarine canyon flanks, it can induce sediment gravity flows that descend along tributary gullies towards the main canyon axis. However, these flows had only been clearly identified in the Palamós Canyon, where they could be recorded synchronously with the passage of the trawling fleet. In this study we also recorded trawl-induced sediment gravity flows in the Blanes Canyon, both synchronously and asynchronously with the passage of trawlers. Increases in particulate matter fluxes in other trawled submarine canyons occurring in absence of natural triggering mechanisms, were not directly associated with bottom trawling because of the lack of direct synchronicity of these events with this human activity. Here we show, however, that the practice of bottom trawling along canyon flanks can not only resuspend and directly trigger sediment gravity flows, but they can also pile up disturbed sediment on steep areas, which can become unstable and collapse afterwards, asynchronically with the passage of trawlers. Our study provides evidence that sediment gravity flows in submarine canyons affected by bottom trawling, where the causal mechanisms are presently unidentified, may potentially be linked to instabilities in sediment originating from recurrent bottom trawling, which can precondition these events.